Political Participation Of Voters With Disabilities In Depok City: A Study Case Participation Level In The 2019 General Election And 2020 Regional Election - Rizqi Amalia; Abdul Gofur (Universitas Sultan Ageng Tirtayasa, 2024)
This research based on the problem of inequality in the number of political participants with disabilities in Depok City between Pemilu 2019 and Pilkada 2020. The research analysis will focus on the differentiating factors that cause an increase in voter participation among people with disabilities by using a case study of Depok City. Through a descriptive analysis of the increase in political participation of people with disabilities in Depok City, this study will reveal the factors that cause the increase in participation of people with disabilities and how election improvement efforts affect people with disabilities. The results of this study show that how candidate pairs try to encourage the participation of voters with disabilities in the 2020 Regional Election in Depok City can increase the number of people with disabilities who vote.